2021
DOI: 10.3390/ijms22095047
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics, microRNA and Metabolic Syndrome: A Comprehensive Review

Abstract: Epigenetics refers to the DNA chemistry changes that result in the modification of gene transcription and translation independently of the underlying DNA coding sequence. Epigenetic modifications are reported to involve various molecular mechanisms, including classical epigenetic changes affecting DNA methylation and histone modifications and small RNA-mediated processes, particularly that of microRNAs. Epigenetic changes are reversible and are closely interconnected. They are recognised to play a critical rol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 209 publications
(248 reference statements)
0
45
0
3
Order By: Relevance
“…The downstream actions include reducing the degree of activation of mTORC1, an important regulator of autophagy, and a driver of the increase in de novo lipid synthesis in the presence of hyperinsulinemia. Ongoing studies are evaluating whether metabolic pathways also coordinate the epigenetic regulation of transcriptional networks, which can occur through reversable methylation of specific cytosines in DNA and through specific methylation and acetylation marks of key lysine within specific histone components of chromatin [ 53 ]. For example, it is known that certain histone marks can pause the differentiation of adipocytes [ 54 ] while modification through NAD + generated by metabolism of α-ketoglutarate can remove these marks and allow differentiation to proceed [ 55 ].…”
Section: New Target For Tzdsmentioning
confidence: 99%
“…The downstream actions include reducing the degree of activation of mTORC1, an important regulator of autophagy, and a driver of the increase in de novo lipid synthesis in the presence of hyperinsulinemia. Ongoing studies are evaluating whether metabolic pathways also coordinate the epigenetic regulation of transcriptional networks, which can occur through reversable methylation of specific cytosines in DNA and through specific methylation and acetylation marks of key lysine within specific histone components of chromatin [ 53 ]. For example, it is known that certain histone marks can pause the differentiation of adipocytes [ 54 ] while modification through NAD + generated by metabolism of α-ketoglutarate can remove these marks and allow differentiation to proceed [ 55 ].…”
Section: New Target For Tzdsmentioning
confidence: 99%
“…An epigenome-wide association study showed that elevated BMI was associated with changes in DNA methylation, mostly in genes involved in lipid and lipoprotein metabolism, substrate transport, and inflammatory pathways and that these alterations are related to adiposity [ 80 ]. Mice deficient in histone demethylase HDM2a, an enzyme responsible for H3K9 demethylation, developed an adult-onset obesity, hypertriglyceridemia, and hypercholesterolemia, as well as insulin resistance compared to wild type controls [ 81 ]. Sirtuins, a class of HDACs, were reported to act as metabolic regulators of glucose homeostasis, insulin resistance, and its associated inflammation.…”
Section: Perspectivesmentioning
confidence: 99%
“…Sirtuins, a class of HDACs, were reported to act as metabolic regulators of glucose homeostasis, insulin resistance, and its associated inflammation. As an example, lack of SIRT1-, SIRT2-, and SIRT6-dependent deacetylation and activation of specific adipose gene programs was shown to contribute to the development of metabolic disorders, such as type 2 diabetes and obesity [ 81 ]. miRNA-mediated epigenetic changes also induce obesity-associated adipose tissue inflammation, a significant factor responsible for developing insulin resistance and type 2 diabetes.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…An early recognition using clinical parameters and inflammatory markers is imperative in order to reduce morbidity and possibly mortality too, attributable to the syndrome. In addition, a number of susceptibility genes and adipokines have been identified that are thought to play a role in the genetic etiology of MetS, thus paving the way to new molecular insights [ 3 , 4 , 5 ]. Knowledge of the etiopathogenic pathways could facilitate novel therapeutic approaches to managing and treating MetS.…”
mentioning
confidence: 99%